2013 Eighth International Conference on Broadband and Wireless Computing, Communication and Applications 2013
DOI: 10.1109/bwcca.2013.23
|View full text |Cite
|
Sign up to set email alerts
|

REECH-ME: Regional Energy Efficient Cluster Heads Based on Maximum Energy Routing Protocol for WSNs

Abstract: In this paper, we propose Regional Energy Efficient Cluster Heads based on Maximum Energy (REECH-ME) Routing Protocol for Wireless Sensor Networks (WSNs) . The main purpose of this protocol is to improve the network lifetime and particularly the stability period of the network. In REECH-ME, the node with the maximum energy in a region becomes Cluster Head (CH) of that region for that particular round and the number of the cluster heads in each round remains the same. Our technique outperforms LEACH which uses … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…Each mobile sink's time for data acquisition can not exceed a maximum value T . Equation (2) reflects that each intermediate sensor node is just visited once for all mobile sinks. Equation (3) reflects the balance principle for the intermediate sensor nodes.…”
Section: Problem Formulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Each mobile sink's time for data acquisition can not exceed a maximum value T . Equation (2) reflects that each intermediate sensor node is just visited once for all mobile sinks. Equation (3) reflects the balance principle for the intermediate sensor nodes.…”
Section: Problem Formulationmentioning
confidence: 99%
“…The distance between nodes ranges from 1 to 10. The number of mobile sink is set in [1][2][3][4][5][6] and its moving speed is 1. For mobile sinks, we define the unit cost of each sink is 10.…”
Section: A Experiments Setupmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, there are a lot of routing protocols in WSN are used that a few of them have considered the requirements of network applications in time critical data transmission is important [8][9][10][11][12][13][14][15]. In wireless sensor network gathers data from the relevant data would reduce the large amounts of data traffic on the network, avoid information overload, creating a more accurate signal and requires less energy than sending all unprocessed data inside the network.…”
Section: Introductionmentioning
confidence: 99%
“…Static clustering along with dynamic cluster head selection [20], [21] during every round in EDAC also saves computation overhead involved in cluster formation again and again. Thus it can be concluded that by implementing static clusters and multi-hop communication between sensor nodes and cluster head using relay nodes would definitely result in load balancing and better connectivity in the entire heterogeneous wireless sensor network.…”
Section: Proposed Edac Algorithmmentioning
confidence: 99%